TOKSISITAS GLISEROL ATAU SUKROSA PADA SEL KHAMIR accharomyces cerevisiae YANG DISEMPAN PADA SUHU RENDAH BEKU - Julistiono, Heddy (BERITA BIOLOGI, 2001)
The effect of cryoprotectants glycerol and sucrose on cell viability and fermentation rate of Saccharomyces cerevisiae after freezing (-30 Â°C) and Chawing (30 Â°C) were studied.Both freezing and thawing were done rapidly. The mortality of cells treated with low concentrations of cryoprotectans (2.5, 5, and 10 %) after 15 and 30 days of cryopreservation, was remarkably higher than that of control and higher concentration (20% and 40%).Glycerol or sucrose with concentration of 20 % and 40 % protected cells from severe mortality only after 90 days of cryopreservation.Fermentation rate of cells treated with 20 % or 40 % of the two cryoprotectants were higher than that of control after 60 and 90 days of cryopreservation.The data indicated that in certain circumstance cryoprotectant could be toxic for the cells during freezing and thawing.Since biomembrane is not permeable to sucrose, therefore we proposed that target of sucrose toxicity may be extracellular, whereas glycerol, which penetrate cells,targets of the toxicity may be both extracellular and intracellular domains.Interaction between cryoprotectant and cell membranes is discussed.